Carbon uptake experiments with a zonally-averaged global ocean circulation model - Stocker, Thomas F.; Broecker, Wallace S.; Wright, Daniel G. (Tellus B: Chemical and Physical Meteorology, 1994)
A model which simulates the zonally averaged thermohaline circulation in the major ocean basins and includes the balance of stable and decaying tracers, is presented. The model is used to estimate oceanic uptake of tracers due to transiently varying atmospheric concentrations, with steady thermohaline circulation. 2 X CO2-experiments with an inorganic carbon cycle component yield an evolution that is consistent with results from 3-dimensional models on time scales of decades to millennia. The model’s average uptake from 1980–1989 is 2.1 Gt C yr-1 when the industrial evolution of pCO2 in the atmosphere is prescribed. Only about 10% of excess carbon is taken up by waters sinking in the North Atlantic but 30% by waters sinking in the Southern Ocean. The influence of vertical and horizontal mixing processes on the uptake in various regions the ocean is investigated. Uptake experiments of bomb-produced radiocarbon demonstrate possible limitations of the model. Agreement with the observations can be obtained if a parameterization is introduced that accounts for the near-surface meridional mixing of tracers due to the wind-driven circulation. Inventories and penetration depth of bomb radiocarbon are compared with estimates from 3-dimensional model simulations and observations. Global uptake is close to these estimates, however, inventories in the Southern Ocean are considerably larger.